Social Media and Libraries:A Scientometric Assessment of World Output, 2003-2014 - Gupta, B. M.; Dhawan, S. M.; Visakhi, P. (Journal of Information and Knowledge, 2016)
The paper examines 1472 global publications on "social media and libraries" covering the period 2003-14 on a series of indicators. The publications output averaged 62% annual growth. These 1472 global publications received 5350 citations since their publication, averaging 1.68 citations per paper. Only 47.55% publications were cited one or more times. The contribution of top most productive countries (namely USA, U.K., Canada, Spain, Germany, China, Australia, India, Netherlands and Singapore) together accounted for 74.86% share. Netherlands registered the highest share (38.89%) of international collaborative papers among the top 10 countries during 2003-14. The top 15 organizations out of 293 accounted for 12.57% share. The top 10 authors out of 410 accounted for 4.96% share during 2003-14. Journals (57%) and conference proceedings (26.09%) contributed the largest share to global output during 2003-14. The top 15 journals contributed 290 publications(34.20%) during 2003-14. The top 10 most highly cited papers received 1094 citations, from 51 to 401 citations per paper. Blogs contributed the largest share (34.99%) of publications among social media sites, followed by Wikipedia (19.97%), Facebook (13.65%) and others.